Challenges and remedies in the efficient usage of quality inputs in schools - a study based on the schools in Tellippalai division - Sasikumar, P.; Nithlavarnan, A. (Research and Development Branch Ministry of Education Sri Lanka, 2016)
Quality inputs for quality education” concept has been considered in teaching – learning in the Sri Lankan education system. There are many issues pertaining to the efficient use of quality inputs. The objectives of the study are to identify the weakness of efficient use of quality inputs and to propose recommendations to promote efficient ways in this process. Eleven schools in the division of Tellippalai among thirty four schools have been chosen for this study. Stratified random sampling method is used for this purpose. Principals, teachers and students have been chosen randomly for the purpose of this study. Questionnaire, observation schedule, Interview schedule and administrative documents have been used for data collection. Collected data have been organized in the form of tables, graphs and percentages for data analysis. The findings in this study show, that there are many issues and problems in relation to efficient use of quality inputs. The problems identified in this study such as inadequate allocation for quality inputs, irregular distribution, timeframe not adopted, negative attitude of principals and teachers, irregular use of inputs, unplanned and weakness procurement, less transparency practices in accounting, needful lists not submitted, abuse of finance, work load, negligence in using inputs, biasness, failure in maintaining documents are identified as factors which are responsible for inefficient use of quality inputs. In future, to ensure the efficient use of quality inputs following actions are required: timely release of quality inputs; changing attitudes of teachers and principals pertaining to quality inputs; timely distribution and procurement; transparency in quality finance; regular supervision and monitory action; promotion of motivation to use quality inputs at school level adequate allocation of time to ensure quality inputs use in curricular management at the school.
Keywords: Quality Inputs; Efficient use of Inputs; Challenges and remedies